Recommendations on the safety and effectiveness of Ketamine for induction to facilitate advanced airway management in head injured patients in South Africa by pre-hospital professionals: A rapid review - Smit, Pierre Christo (Division of Emergency Medicine, 2017)
Background: The South African 2006 Advanced Life Support and Emergency Care Practitioner protocols do not currently reflect the latest, best evidence-based practices for emergency care, specifically regarding induction agents in head injury patients. Recent evidence has challenged some preconceptions regarding the use and safety of Ketamine in head injuries. In response to this, the Health Professions Council of South Africa Professional Board for Emergency Care (HPCSA PBEC) has requested a review of the emergency care protocols. Objectives: To determine the evidence of effectiveness and safety of intravenous/intraosseous (IV/IO) Ketamine as an induction agent for adult patients with traumatic brain injury, the authors aimed to determine the all-cause mortality at 30 days, adverse events/effects, morbidity and rate of successful intubation associated with ketamine administration, as compared to standard induction agents. Research Question: What is the evidence of effectiveness and safety of IV/IO Ketamine in adult patients with head injury, for pre-hospital induction in advanced airway management, compared to standard therapy? Methods: The review followed a tiered approach, where three different tiers of searches were performed for articles relevant to the research question. Two authors independently and in induplicate performed title, abstract and full-text review for each potentially included article, as well as critical appraisal of 3 CPGs found in the tier 1 searches. Tier 1 searched for Clinical Practice Guidelines (CPGs), tier 2 for Systematic Reviews (SRs) and tier 3 for Randomised Controlled Trials (RCTs) relating to the research question. No grey literature searches were performed, but reference lists of included articles were searched for relevant articles. Main Results: The authors could not find any studies to include (CPGs, SRs or RCTs) in this review which would answer the research question. However, several articles were found which describe ketamine use in the Intensive Care Unit (ICU) and surgical patients with regards to intracranial pressure, cerebral perfusion pressure and general haemodynamic effects. Another article (RCT) was found which used ketamine as an induction agent compared to etomidate to facilitate intubation in critically ill patients. These articles provide some helpful insights as to ketamine's effectiveness and safety for induction to facilitate intubation in traumatic brain injury patients in the pre-hospital setting. Conclusions: The authors could not make any recommendations regarding the research question, and the safety and effectiveness of ketamine for induction to facilitate intubation in adult traumatic brain injury remains unclear. A lack of empirical evidence at RCT level has led to substantial knowledge gaps regarding our understanding of Ketamine and its effects in traumatic brain injury patients.